LINGUISTIC PROBLEMS FOUND IN CURRICULUM VITAE WRITTEN BY EFL STUDENTS IN ENGLISH FOR OFFICE COURSE - Aulia Andhini; Hafni Hafsah; Egi Raputri (Al-Irsyad: Journal of Education Science, 2026)
This study aims to investigate linguistic problems found in curriculum vitae written by English as a Foreign Language (EFL) students enrolled in an English for Office course. Curriculum vitae is an essential professional document that reflects students’ readiness to enter the workplace; however, many EFL students still encounter difficulties in producing accurate and appropriate language for professional purposes.This research use a qualitative descriptive design using document analysis. The Participants were 15 of third semester of the English Education Study Program at Institut Az Zuhra. The data consisted of 15 curriculum vitae documents written, which analyzed by identifying, classifying, and calculating the frequency of linguistic problems, which were categorized into grammar, vocabulary, and mechanics. The findings showed that grammatical problems were the most frequent, representing for 45 errors (50%),  followed by vocabulary misuse with 32 errors (35%) and mechanical errors with 23 errors (15%). These results indicate that students still lack mastery of formal written English required for professional documents. The study suggests that English for Office instruction should emphasize grammar accuracy, appropriate word choice, and exposure to authentic professional language.